2011
DOI: 10.1111/j.1365-2265.2011.04124.x
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality and morbidity in Cushing’s syndrome in New Zealand

Abstract: CS is associated with both high mortality and a high prevalence of co-morbidities, even when biochemical cure rates are between 80% and 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 14 publications
(56 reference statements)
10
160
4
1
Order By: Relevance
“…The median of 2 years from symptom-onset to diagnosis found in our study is identical to that reported in a recent study from the European Registry on Cushing's Syndrome (ERCUSYN) (6) and another retrospective study on CS by Bolland et al (5), but in these studies symptomonset was rated by physicians on the basis of chart records. The fact that more than half of the patients of this study were diagnosed within 1 year from first physician contact (median of 1 year from first doctor visit to diagnosis) speaks for an improved awareness of this disease entity within the last years.…”
Section: European Journal Of Endocrinologysupporting
confidence: 78%
See 1 more Smart Citation
“…The median of 2 years from symptom-onset to diagnosis found in our study is identical to that reported in a recent study from the European Registry on Cushing's Syndrome (ERCUSYN) (6) and another retrospective study on CS by Bolland et al (5), but in these studies symptomonset was rated by physicians on the basis of chart records. The fact that more than half of the patients of this study were diagnosed within 1 year from first physician contact (median of 1 year from first doctor visit to diagnosis) speaks for an improved awareness of this disease entity within the last years.…”
Section: European Journal Of Endocrinologysupporting
confidence: 78%
“…The diagnostic latency of Cushing's syndrome (CS) in general is reported with a median of 2 years in two recent studies, but studies which focus exclusively on the latency between symptom occurrence and diagnosis of pituitary-dependent CD are lacking so far (5,6). Also, no data exist which elucidate the reasons for the long diagnostic process of patients with CD or CS.…”
Section: Introductionmentioning
confidence: 99%
“…SMR was shown to be increased to 3.73 in patients with persistent Cushing's disease after transsphenoidal surgery (22). Furthermore, persistently increased mortality had been reported even after long-term biochemical remission (23,24). In a recent study, cardiovascular risk was found to be persistent despite dramatic improvements in body composition abnormalities (25).…”
Section: Discussionmentioning
confidence: 97%
“…bolus of 250 mg synthetic ACTH (Synacthen 0.25 mg/ml; Novartis Healthcare) at 0800 h. Venous blood was drawn through an indwelling catheter at 0, 30, and 60 min after ACTH administration for the determination of 17-OHP and 11-S. On the luteal phase of the cycle (menstrual days [22][23][24], progesterone was measured.…”
Section: Materials and Protocolsmentioning
confidence: 99%
“…The fact that the diagnosis of Cushing's syndrome is often delayed by several years (1,2) is not surprising, given that the early features are characteristically non-specific. However, detection in this pre-clinical phase offers the theoretical potential to prevent Cushing's syndrome or reduce cortisol levels, which may otherwise act to accelerate cardiovascular disease (through blood pressure, lipids, and dysglycaemia) and ageing (through atrophic effects on skin, muscle and bone) and also have adverse neurocognitive effects.…”
mentioning
confidence: 99%